A case-crossover study of heat exposure and injury risk among outdoor construction workers in Washington State - Calkins, Miriam M.; Bonauto, David; Hajat, Anjum; Lieblich, Max; Seixas, Noah; Sheppard, Lianne; Spector, June T. (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVES ': 'The primary objective of this study was to assess the relationship between heat exposure and occupational traumatic injuries among construction workers. ' ' METHODS ': 'We assessed the relationship between humidex, a measure of apparent temperature, and Washington State Fund workers’ compensation injuries among outdoor construction workers using a case-crossover design with time-stratified referent selection. Warm month (March–October) adult outdoor construction traumatic injury claims from 2000–2012 were spatiotemporally joined with high-resolution meteorological data. We used conditional logistic regression with linear splines to assess the association between maximum daily humidex and injuries. ' ' RESULTS ': 'There were 63 720 occupational traumatic injury claims in construction that met our eligibility criteria during the study period. The traumatic injury odds ratio (OR) was 1.005 [95% confidence interval (CI) 1.003–1.007] per one °C change in humidex. In the spline analyses, we observed a nearly linear association of humidex with the risk of a traumatic injury. Effect estimates were higher among younger (18–24 years) and older (>54 years) workers, workers with lower extremity injuries, workers with less job experience, smaller employers, workers working in Western Washington, and time of injury before 12:30 hours, although CI of effect estimates overlapped in stratified analysis categories. ' ' CONCLUSIONS ': 'In this study of Washington outdoor construction workers, increasing maximum daily humidex was associated with increasing traumatic injury risk. Further work should explore mechanisms of the association between heat exposure and traumatic injuries. Injury prevention efforts targeted at construction should address heat-related risk factors. In addition, heat awareness campaigns should address outcomes beyond heat-related illness.
Keywords: case-crossover study; construction; construction industry; construction worker; heat exposure; heat stress; humidex; injury; injury risk; meteorological data; occupational injury; outdoor construction worker; traumatic injury; USA; Washington State; worker compensation